Sericulture in Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Each month from October to April, three boxes of silkworm eggs arrive at the Herbert Chitepo Training Centre in Zimbabwe from India. Two years ago IT launched a pilot project in Zimbabwe which is now progressing well. On previously infertile land a...